2015
DOI: 10.1111/jvs.12341
|View full text |Cite
|
Sign up to set email alerts
|

A plant economics spectrum in Mediterranean forests along environmental gradients: is there coordination among leaf, stem and root traits?

Abstract: Questions: Is there any evidence of coordination among leaf, stem and root traits, and thereby of the existence of a plant economics spectrum at the species and community level in Mediterranean forests? Are these traits related to plant size and seed mass?Location: Mediterranean forests and shrublands, Sierra Morena mountains, C ordoba, southern Spain. Methods:We selected nine woody plant communities along a natural local gradient of soil water and nutrient availability. We measured key leaf, stem, root and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
108
3
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 71 publications
17
108
3
10
Order By: Relevance
“…This result might be caused by different adaptations of shrubs and trees to environmental gradients, and we gave some explanations below. Our results (located in the continental monsoon climate zone) were consistent with those found by previous studies, which were primarily conducted in the Mediterranean climate zones [18][19][20]26]. This consistency across different climate zones and growth forms strengthened the evidence of widely existing leaf community economics spectrum.…”
Section: The Leaf Community Economics Spectrumsupporting
confidence: 82%
See 3 more Smart Citations
“…This result might be caused by different adaptations of shrubs and trees to environmental gradients, and we gave some explanations below. Our results (located in the continental monsoon climate zone) were consistent with those found by previous studies, which were primarily conducted in the Mediterranean climate zones [18][19][20]26]. This consistency across different climate zones and growth forms strengthened the evidence of widely existing leaf community economics spectrum.…”
Section: The Leaf Community Economics Spectrumsupporting
confidence: 82%
“…The strong coordination of LES traits at the community level indicated the existence of a leaf community economics spectrum across trees and shrubs, which could be one part of plant community economics spectrum [18,19]. In addition, we found that the relationships of LES traits at both community levels were stronger than species level.…”
Section: The Leaf Community Economics Spectrummentioning
confidence: 61%
See 2 more Smart Citations
“…The relatively strong correlations between the only stem trait, wood density (WD), and the three leaf traits N green , LMA and LHL suggest that the observed trait syndromes can be extended to a leaf-stem economics. Such a trait coordination across organs is supported by many [4853] studies, although there are exceptions [12, 46, 54, 55]. Reich [56] has argued that such a coordinated change in traits reflects a whole-plant strategy of “fast” vs. “slow” growth.…”
Section: Discussionmentioning
confidence: 99%